PENGARUH PENDAPATAN PERKAPITA DAN INVESTASI PMDN TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN KOTA JAMBI - Sabyan, Muhammad; Mainita, Mainita; Widyanti, Rina (Universitas Muhammadiyah Jambi, 2022)
This study aims to see how the influence of per capita income and foreign investment investment in land and building tax revenues in the city of Jambi, and the results of research that have been conducted found that per capita income is positive, namely 238,773 meaning that every time there is an increase in per capita income of 1 rupiah, it will increase land and building tax income by 238,773 rupiah assuming other independent variables have a fixed value, for the PMDN investment variable the coefficient value is -34.875 with a negative value, meaning that if PMDN investment increases by 1 rupiah then land and building tax revenue will move down by 34.875 with the assumption the other variables are constant. By looking at the effect of per capita income on land and building tax receipts that can provide a positive value, the Jambi city government should play an active role in trying to increase the per capita income of the Jambi city community which can have an effect on land and building tax revenues.